Working and Caring: The Simultaneous Decision of Labor Force Participation and Informal Elderly and Child Support Activities in Mexico - van Gameren, Edwin; Velandia Naranjo, Durfari (Pontificia Universidad Católica de Chile, 2015)
We analyze factors determining women’s decisions to participate in the labor market and provide elderly care and nonfinancial support to their (grand)children. We use data from the Mexican Health and Aging Study, a survey of people aged 50 and over, applying a three-equation, reducedform SUR model. Results suggest that care needs are the driving force behind caregiving activities. Traditional roles also appear to be relevant in the labor force participation decision: women with a closer labor market connection when they were young are more likely to work. Simulations of demographic changes illustrate potential ef fects for future caregiving and participation rates.

Analizamos los factores que determinan la decisión de las mujeres de participar en la mercado laboral y proporcionar cuidados de personas mayores y apoyo no financiero a sus (nietos) hijos. Usamos datos del Estudio Mexicano de Salud y Envejecimiento, una encuesta a personas de 50 años y más, aplicando un modelo SUR de forma reducida de tres ecuaciones. Los resultados sugieren que las necesidades de atención son la fuerza impulsora detrás de las actividades de cuidado. Los roles tradicionales también parecen ser relevantes en la decisión de participación en la fuerza laboral: mujeres con un mercado laboral más cercano conexión cuando eran jóvenes tienen más probabilidades de trabajar. Simulaciones de Los cambios demográficos ilustran los efectos potenciales para el cuidado futuro y tasas de participación.
Keywords: Mujeres - Mercado laboral - México; Women - Labor market - Mexico; Niños y ancianos - México; Children and older people - Mexico; Encuestas ocupacionales - México; Occupational surveys - Mexico; Labor force participation; Elderly care; Care for (grand)children; Multigenerational households; Seemingly unrelated regression model